THE CASE OF THE REHABILITATION OF “URBINO 2” DWELLINGS: A DEMONSTRATION OF THE NEED FOR INTERDISCIPLINARY COOPERATION BETWEEN CRIMINOLOGY AND ’ BUILDING DESIGN’ - Barboni, Rita Maria; Montagna, Emanuele (European Scientific Journal, ESJ, 2013)
On the level of quality of life in the cities, street crimes play a relevant role because the safety of citizens is involved. It is a world-wide problem that is now increasing in relation to a number of factors, among them the new migrations, the level of maintenance of the towns, the level of community policing. The solution is of course a town designed on the basis of crime prevention through environmental design, and on this direction are acting some towns, for a limited part of them, due to the costs of the intervention. The “Urbino 2” district lays at about 15 km from the town (and University) of Urbino, and was originated from planning mistakes of private builders and public administrations as well. As a consequence the only residents became non Cee people who could rent the apartments for very cheap prices, commonly living in greater number than allowed for the apartment or renting a part of it to other poorer people, thus reducing the value of the building, and putting the owners in the condition of being unable to pay for maintenance, and perhaps not willing to do. From a recent survey on a population of 600 persons only 10 are Italians. The district has become a real slum, where the different populations follow the rules and habits of their original countries, thus originating brawls, violence, aggressions and so on. The paper shows the problems arosen in this incorrectly born district near Urbino, and the possibilities offered by CPTED design for its rehabilitation.